The effect of aromatherapy on post-stroke depression: study protocol for a pilot randomized controlled trial - Li, Yujia; Hu, Zekai; Zhou, Kun; Wang, Yanyu; Zhang, Xinglin; Xue, Han; Hu, Jun; Wang, Jie (Frontiers in Psychiatry, 2024)
Background: Post-stroke depression (PSD) is a prevalent psychiatric disorder affecting about onethird of stroke survivors, significantly hindering recovery and quality of life. PSD also imposes a substantial burden on caregivers and healthcare systems. Aromatherapy has shown promise in alleviating depression, anxiety, and sleep disorders. This pilot randomized controlled trial aims to assess the feasibility and preliminary efficacy of mixed herb aromatherapy in treating PSD.Feasibility outcomes encompass recruitment, intervention adherence, assessment completion and safety assessment. Secondary outcomes include evaluations of depression, anxiety, cognitive function, sleep quality, quality of life, and brain function using EEG and fNIRS.Methods: This single-blind pilot randomized controlled trial will be conducted at the Second Rehabilitation Hospital of Shanghai, enrolling ninety-nine post-stroke patients with PSD. Participants will be randomized into three groups: a Non-Active Control Group receiving standardized rehabilitation therapy, a CBT Group receiving conventional rehabilitation with bi-weekly CBT sessions, and an Aromatherapy Group receiving conventional rehabilitation with daily aromatic inhalation sessions.Interventions will last for four weeks, with efficacy assessed at baseline, postintervention, and one month post-intervention. Rating scales will be used to measure changes in depression, sleep quality, cognitive function, and quality of life. EEG and fNIRS will specifically be used to measure changes in cerebral cortex activity and their correlations with depression. Feasibility will be evaluated through recruitment, intervention adherence, assessment completion and safety assessment.Discussion: This pilot study highlights the potential of mixed herb aromatherapy inhalation for treating PSD, addressing limitations of CBT by promoting self-management. While demonstrating feasibility through recruitment, adherence,assessment completion and safety assessment, the study also acknowledges limitations such as unequal intervention times, the lack of physical function data.And the use of culturally relevant plant powders may enhance compliance but limits generalizability. Despite these constraints, the study provides valuable preliminary data and insights into the mechanisms of aromatherapy, encouraging further research and development of effective PSD treatments.